Neuroprotective protein hydrolysates from hemp (Cannabis sativa L.) seeds. Issue 10 (2nd October 2019) - Rodriguez-Martin, Noelia M.; Toscano, Rocio; Villanueva, Alvaro; Pedroche, Justo; Millan, Francisco; Montserrat-de la Paz, Sergio; Millan-Linares, Maria C.
Abstract : Hemp ( Cannabis sativa L.) seeds are well known for their potential use as a source of nutrients, fiber, and bioactive compounds. Abstract : Hemp ( Cannabis sativa L.) seeds are well known for their potential use as a source of nutrients, fiber, and bioactive compounds. A hemp protein isolate, prepared from defatted hemp flour, was hydrolyzed by alcalase and flavourzyme under specific conditions. The resulting hydrolysates were evaluated for the selection of potentially bioactive hemp protein hydrolysates (HPHs) owing to their DPPH scavenging and ferric reducing antioxidant power activity. In vitro cell-free experiments led to the identification of two bioactive HPHs, HPH20A and HPH60A + 15AF, which were used at 50 and 100 μg mL −1 on BV-2 microglial cells in order to evaluate the anti-neuroinflammatory activities. Our results showed that HPH20A and HPH60A + 15AF down-regulated TNF-α, IL-1β, and IL-6 mRNA transcriptional levels in LPS-stimulated BV-2 microglial cells. In addition, HPH20A and HPH60A + 15AF up-regulated the gene expression of anti-inflammatory cytokine IL-10. This study suggests for the first time that HPHs may improve the neuroinflammatory and inflammatory states, supporting the nutraceutical value of hemp seeds.